Teacher Perspectives on the Development of Project-Based Mathematics Modules for Primary Schools in Indonesia's Merdeka Curriculum - Astuti, Dian Anggraeni Tri; Zabit, Mohd Nazir Bin MD (Jurnal Riset Pendidikan Matematika, 2024)
This research aims to analyze teachers' needs for developing a project-based mathematics learning pedagogy module (PjBL) in grade 2 elementary schools in the Indonesian Merdeka Curriculum. This study involved 884 Phase A teachers (grades 1 and 2) in West Java. We collected data through a questionnaire that measured teachers' needs in developing PjBL-based mathematics teaching modules. The results showed that 81% of teachers expressed a high need for developing PjBL-based mathematics teaching modules, with an average score of 4.23 to 4.27, indicating they are at the agreeable or excellent stage. This result showed that teachers need the module to improve their ability to implement project-based learning in the mathematics classroom. Number and geometry themes were teachers' main choices when developing PjBL-based mathematics modules. The needs analysis results recommend the development of a PjBL-based mathematics teaching module for grade 2 primary school teachers in improving project-based teaching practices to foster 21st-century skills, namely the 4Cs, in accordance with the educational objectives of the Merdeka Curriculum in Indonesia.